Bioengineered cardiovascular bypass grafts via in vivo self-assembly of scaffold-guided tubular tissue in rats - Shiqi Hu; Xiuhong Sun; Rui Zhou; Kai Fu; Yunfei Mo; Jialin Xu; Xiaoyan Shen; Shiwen Liu; Yuqing Niu (Journal of Nanobiotechnology)
Abstract Cardiovascular bypass grafting remains a crucial therapeutic approach for complex atherosclerotic diseases. However, the clinical application of traditional grafts is hampered by limited autologous vessel availability, while the translational potential of fully cellular self-assembled vascular grafts is constrained by their prolonged fabrication. Here, we present a scaffold-guided in vivo tubular tissue self-assembly strategy to rapidly engineer functional cardiovascular bypass grafts. Using 3D-printed biodegradable scaffolds implanted subcutaneously in SD rats, we generated bioengineered tubular vascular constructs (BTCs) rich in host cells and extracellular matrix within 2 weeks. BTC exhibited biophysical and biochemical properties highly analogous to the native abdominal aorta. When used as interpositional grafts in the abdominal aorta, the BTCs demonstrated excellent patency, blood flow velocity, vascular reactivity, compliance, and histological architecture comparable to those of the native vessel over a 24-week implantation period. Our method significantly shortens the fabrication time of bioengineered vessels—from several months to two weeks—thereby aligning with the critical time window required for elective cardiovascular bypass surgery. Moreover, all materials used in this study are clinically approved, which facilitates future clinical translation. This work establishes a practical and scalable platform for the rapid, “off-the-shelf” production of bioengineered cardiovascular grafts through stable scaffold-guided in vivo tissue formation. Graphical abstract